∑ n = 4 2 0 ( n ) ! ( n − 4 ) !
If the result of the summation above can be written in form b a for a and b are positive, coprime integers, find a + b
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
n = 4 ∑ 2 0 n ! ( n − 4 ) ! = n = 4 ∑ 2 0 n ( n − 1 ) ( n − 2 ( n − 3 ) 1 = n = 4 ∑ 2 0 n ( n − 3 ) ( n − 1 ) ( n − 2 ) 1 = n = 4 ∑ 2 0 ( n 2 − 3 n ) ( n 2 − 3 n + 2 ) 1 Note: n 2 − 3 n 1 − n 2 − 3 n + 2 1 = ( n 2 − 3 n ) ( n 2 − 3 n + 2 ) 2 = 2 1 n = 4 ∑ 2 0 ( n ( n − 3 ) 1 − ( n − 1 ) ( n − 2 ) 1 ) = 2 1 n = 4 ∑ 2 0 [ 3 1 ( n − 3 1 − n 1 ) − ( n − 2 1 − n − 1 1 ) ] = 2 1 [ 3 1 ( n = 1 ∑ 1 7 n 1 − n = 4 ∑ 2 0 n 1 ) − ( n = 2 ∑ 1 8 n 1 − n = 3 ∑ 1 9 n 1 ) ] = 2 1 [ 3 1 ( 1 1 + 2 1 + 3 1 − 1 8 1 − 1 9 1 − 2 0 1 ) − ( 2 1 − 1 9 1 ) ] = 2 1 [ 3 1 ( 3 4 2 0 3 4 2 0 + 1 7 1 0 + 1 1 4 0 − 1 9 0 − 1 8 0 − 1 7 1 ) − ( 3 8 1 9 − 2 ) ] = 2 1 [ 3 1 ( 3 4 2 0 5 7 2 9 ) − 3 8 1 7 ] = 2 0 5 2 0 5 7 2 9 − 2 8 8 1 7 = 2 0 5 2 0 1 1 3 9
⇒ a + b = 1 1 3 9 + 2 0 5 2 0 = 2 1 6 5 9
Problem Loading...
Note Loading...
Set Loading...
The summation itself is
∑ n = 4 2 0 n ! ( n − 4 ) !
= ∑ n = 4 2 0 n × ( n − 1 ) × ( n − 2 ) × ( n − 3 ) × ( n − 4 ) ! ( n − 4 ) !
= ∑ n = 4 2 0 n × ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1
Notice that
( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1 − n × ( n − 1 ) × ( n − 2 ) 1
= n × ( n − 1 ) × ( n − 2 ) × ( n − 3 ) ( n ) − ( n − 3 )
= n × ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 3
So
n × ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1 = 3 1 × ( ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1 − n × ( n − 1 ) × ( n − 2 ) 1 )
Then substitute that to the summation
∑ n = 4 2 0 n × ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1 = ∑ n = 4 2 0 3 1 × ( ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1 − n × ( n − 1 ) × ( n − 2 ) 1 )
= 3 1 × ( ∑ n = 4 2 0 ( n − 1 ) × ( n − 2 ) × ( n − 3 ) 1 − n × ( n − 1 ) × ( n − 2 ) 1 )
= 3 1 × ( ( 3 × 2 × 1 1 − 4 × 3 × 2 1 ) + ( 4 × 3 × 2 1 − 5 × 4 × 3 1 ) + . . . + ( 1 9 × 1 8 × 1 7 1 − 2 0 × 1 9 × 1 8 1 )
Use the telescopics, then it will remain
3 1 × ( 3 × 2 × 1 1 − 2 0 × 1 9 × 1 8 1 )
= 3 1 × ( 6 1 − 6 8 4 0 1 )
= 3 1 × 6 8 4 0 1 1 4 0 − 1
= 3 1 × 6 8 4 0 1 1 3 9
= 2 0 5 2 0 1 1 3 9
1139 and 20520 are coprime, so a = 1 1 3 9 and b = 2 0 5 2 0 , then a + b = 2 1 6 5 9
*cmiiw